Calmodulin mutations affecting Gly114 impair binding to the NaV1.5 IQ-domain - Malene Brohus; Ana-Octavia Busuioc; Reinhard Wimmer; Mette Nyegaard; Michael Toft Overgaard (Frontiers Media S.A., 2023)
Missense variants in CALM genes encoding the Ca2+-binding protein calmodulin (CaM) cause severe cardiac arrhythmias. The disease mechanisms have been attributed to dysregulation of RyR2, for Catecholaminergic Polymorphic Ventricular Tachycardia (CPVT) and/or CaV1.2, for Long-QT Syndrome (LQTS). Recently, a novel CALM2 variant, G114R, was identified in a mother and two of her four children, all of whom died suddenly while asleep at a young age. The G114R variant impairs closure of CaV1.2 and RyR2, consistent with a CPVT and/or mild LQTS phenotype. However, the children carrying the CALM2 G114R variant displayed a phenotype commonly observed with variants in NaV1.5, i.e., Brugada Syndrome (BrS) or LQT3, where death while asleep is a common feature. We therefore hypothesized that the G114R variant specifically would interfere with NaV1.5 binding. Here, we demonstrate that CaM binding to the NaV1.5 IQ-domain is severely impaired for two CaM variants G114R and G114W. The impact was most severe at low and intermediate Ca2+ concentrations (up to 4 µM) resulting in more than a 50-fold reduction in NaV1.5 binding affinity, and a smaller 1.5 to 11-fold reduction at high Ca2+ concentrations (25-400 µM). In contrast, the arrhythmogenic CaM-N98S variant only induced a 1.5-fold reduction in NaV1.5 binding and only at 4 µM Ca2+. A non-arrhythmogenic I10T variant in CaM did not impair NaV1.5 IQ binding. These data suggest that the interaction between NaV1.5 and CaM is decreased with certain CaM variants, which may alter the cardiac sodium current, INa. Overall, these results suggest that the phenotypic spectrum of calmodulinopathies may likely expand to include BrS- and/or LQT3-like traits.